2016
DOI: 10.1002/cre2.35
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral appliance for obstructive sleep apnea patients

Abstract: Although oral appliances (OAs) have become widely used for the management of obstructive sleep apnea (OSA), side effects of OAs are generally related to poor utilization. The purpose of the present study was to evaluate relationship between utilization and treatment efficacy of a boil‐and‐bite appliance for OSA patients. A total of 135 patients with OSA who had used an OAs were mailed a questionnaire to determine whether they were currently using the OA. If so, they were asked about OA use, improvement of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In most publications, both drooling and xerostomia have been described as common side effects of MADs. 22,38,[55][56][57][58][59][60][61][62][63][64][65][66] The side effects are often mild and transient, and they improve as patients continue to use their appliance. 59,61,62…”
Section: The Association Between Mad and Selfreported Omdmentioning
confidence: 99%
See 2 more Smart Citations
“…In most publications, both drooling and xerostomia have been described as common side effects of MADs. 22,38,[55][56][57][58][59][60][61][62][63][64][65][66] The side effects are often mild and transient, and they improve as patients continue to use their appliance. 59,61,62…”
Section: The Association Between Mad and Selfreported Omdmentioning
confidence: 99%
“…As described in the Results, oral appliance side effects like drooling and xerostomia are frequently reported. 22,38,[55][56][57][58][59][60][61][62][63][64][65][66] Surprisingly, many included studies showed that drooling and dry mouth due to the use of MAD are often mild 59,61,62 and can be decreased with regular use and fit adjustment. 66,82 Studies have shown that after 4-6 weeks of MAD wear, the majority of these side effects diminish.…”
Section: The Association Between Mad and Selfreported Omdmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who continued to use their OAs exhibited improved polysomnography (PSG) results and fewer subjective symptoms. However, hypersalivation, dry mouth, and pain and discomfort in the temporomandibular joint were reported as side effects (Makihara et al, 2016 ). The most common reasons for OA discontinuation were the associated side effects and the lack of treatment effectiveness (Makihara et al, 2016 ; McGown et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few research papers [4][5][6][7][8] do however address the topic of boil and bite appliances. It must be recognized that the patients involved in these studies had all been medically evaluated by sleep physicians and qualified dentists had examined them to make sure they would be good candidates for oral appliance therapy.…”
mentioning
confidence: 99%